1991
DOI: 10.1073/pnas.88.18.8020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stimulation-G protein subunit coupling by using active insulin-like growth factor II receptor peptide.

Abstract: The peptide Arg2"'0-Lys2423 (peptide 14) of the human insulin-like growth factor il/mannose 6-phosphate receptor directly activates G12, a GTP-bnding protein (G protein), and is responsible for G1.2 activating function of the receptor. To characterize the basic mechanism of couplings between receptor stimulation and subunits of G proteins, we constructed a system consisting of peptide 14 and a and Ay subunits of G1.2 in aqueous solution. Peptide 14 significantly increased the rate of guanosine 5'-[y-thio]triph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Several investigations have shown that IGF2R interacts with the Ga protein to affect cell behaviors by activating specific intracellular signaling cascades (Okamoto & Nishimoto 1991, McKinnon et al 2001, Hawkes et al 2006. Conversely, in mouse L-cell membranes and phospholipid vesicles, IGF2R is not able to interact with a small G-protein (Korner et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigations have shown that IGF2R interacts with the Ga protein to affect cell behaviors by activating specific intracellular signaling cascades (Okamoto & Nishimoto 1991, McKinnon et al 2001, Hawkes et al 2006. Conversely, in mouse L-cell membranes and phospholipid vesicles, IGF2R is not able to interact with a small G-protein (Korner et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, IGF2 to IGF1R or InR triggers a series of mitotic signaling cascades that function in cell development, growth, survival, and metabolic effect regulation ( Jones & Clemmons 1995, Diaz et al 2007, Blum & Baumrucker 2008. Recent evidence has shown that in spite of degrading IGF2 in the lysosome, IGF2R may spark intracellular signaling cascades in cell behavior regulation (Okamoto & Nishimoto 1991, McKinnon et al 2001, Hawkes et al 2006, but the function of IGF2R in signaling transduction in the heart remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in Balb/c3T3 or Chinese hamster ovary cells, IGF-II by stimulating its receptor has been shown to increase calcium influx via activation of Gi (Nishimoto et al, 1987a;Matsunaga et al, 1988;Okamoto et al, 1991a). The coupling of the IGF-II receptor to Gi was also demonstrated in reconstituted phospholipid vesicles (Nishimoto et al, 1989;Murayama et al, 1990;Okamoto et al, 1990a) and a region comprising 14 amino acids within the IGF-II receptor was identified as the G protein-activating sequence (Okamoto et al, 1990a;Okamoto and Nishimoto, 1991). Indeed, substitution of amino acids within this region changes the specificity of the coupling between IGF-II receptor and G proteins .…”
mentioning
confidence: 98%
“…Moreover, the existence of a putative G-protein-binding site within the cytoplasmic domain of the IGF2R suggests that IGF-II may regulate small G proteins that activate signaling pathways through IGF2R (Nishimoto et al 1989, Murayama et al 1990, Okamoto & Nishimoto 1991, Ikezu et al 1995. Based on these findings, we propose that the binding of IGF-II to IGF2R may trigger an intracellular signaling cascade response to cardiac hypertrophy and that the role of this signaling is completely different from that of IGF1R-derived physiological hypertrophy.…”
Section: Introductionmentioning
confidence: 99%